The brazilian elderly population and alcohol consumption: An integrative review (Research, Society and Development, 2025)
The demographic shift in Brazil, marked by a growing elderly population, has brought about increased attention to the health outcomes of older adults. Alcohol consumption is an associated risk factor. Although traditionally more prevalent in younger age groups, recent studies have revealed an upward trend in alcohol consumption among the elderly, representing an emerging public health concern. However, studies focusing on the elderly are limited, as the majority of investigations have concentrated on younger age groups. This integrative review was conducted to analyze existing research on patterns of alcohol use among elderly individuals in Brazil, highlighting the strong associations between alcohol use in older adults and variables such as sex, ethnicity, age, education, socioeconomic status, health status, and tobacco use. National data indicate an increase in alcohol use among older adults, but there are still barriers to fully analyzing the current patterns. Furthermore, the review found no consistent evidence connecting alcohol intake with chronic diseases or oral health complications in the elderly population. Nevertheless, evidence suggests an association with declining physical performance. No study has addressed the psychological impact of alcohol consumption on the elderly.